Efficient Z-Scheme Photocatalyst for Hydrogen Production via Water Splitting Using CH3- and F-Modified C60 Fullerene-Based Heterostructures - Wan, Xue-Qing; Yang, Chuan-Lu; Shi, Wen-Jie; Li, Xiaohu; Liu, Yuliang; Zhao, Wenkai; Gao, Feng (Small (Weinheim an der Bergstrasse, Germany), 2025)
The ability to drive overall water splitting and efficiently utilize carriers is critical for optimizing photocatalytic performance to promote hydrogen production. Modifying photocatalysts with functional groups such as F and CH3 can significantly enhance these capabilities. Our results show that the large electrostatic potential at the surfaces of CH3@C60/ZrS2, F@qHP-C60/GeC, and F@qHP-C60/Bi heterostructures not only improves carrier separation but also increases the overpotentials for both the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER). Moreover, the Gibbs free energies (ΔG) for HER and OER are notably reduced, due to a more localized charge density distribution that facilitates the spontaneous occurrence of these reactions. Non-adiabatic molecular dynamics simulations demonstrate that the smaller band gaps in these CH3 and F-modified C60-based heterostructures can result in faster electron-hole (e-h) recombination and enhanced carrier lifetime. These improvements contribute to a more efficient Z-scheme and superior carrier separation. In short, compared to the unmodified structures, the incorporation of radicals enhances the ability to drive HER and OER spontaneously, reduces ΔG, strengthens thermodynamic stability, accelerates e-h recombination, and increases the visible light absorption coefficient; all of the above contribute to the possibility of heterostructures becoming promising photocatalysts. This work introduces novel high-performance photocatalysts and offers valuable insights for developing efficient photocatalysts based on C60 and qHP-C60 monolayers.The ability to drive overall water splitting and efficiently utilize carriers is critical for optimizing photocatalytic performance to promote hydrogen production. Modifying photocatalysts with functional groups such as F and CH3 can significantly enhance these capabilities. Our results show that the large electrostatic potential at the surfaces of CH3@C60/ZrS2, F@qHP-C60/GeC, and F@qHP-C60/Bi heterostructures not only improves carrier separation but also increases the overpotentials for both the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER). Moreover, the Gibbs free energies (ΔG) for HER and OER are notably reduced, due to a more localized charge density distribution that facilitates the spontaneous occurrence of these reactions. Non-adiabatic molecular dynamics simulations demonstrate that the smaller band gaps in these CH3 and F-modified C60-based heterostructures can result in faster electron-hole (e-h) recombination and enhanced carrier lifetime. These improvements contribute to a more efficient Z-scheme and superior carrier separation. In short, compared to the unmodified structures, the incorporation of radicals enhances the ability to drive HER and OER spontaneously, reduces ΔG, strengthens thermodynamic stability, accelerates e-h recombination, and increases the visible light absorption coefficient; all of the above contribute to the possibility of heterostructures becoming promising photocatalysts. This work introduces novel high-performance photocatalysts and offers valuable insights for developing efficient photocatalysts based on C60 and qHP-C60 monolayers.